Role of vegan and vegetarian diets in type 2 diabetes - Dagna Siedlecka; Wojciech Micał; Ewa Krzewicka-Romaniuk; Anna Pradiuch (Kazimierz Wielki University, 2019)
Significant benefits could be achieved in diabetes management with vegetarian and vegan diets. Many reports in literature indicate that both, vegetarian and vegan diet bring a potential benefits in a treatment of type 2 diabetes. What is more vegetarian and vegan diets have a positive effect on anti-atherogenic process. Observational studies indicate that risk of developing diabetes is reduced by half in people during a vegetarian diet, compared to non-vegetarian.